IMPROVEMENT OF METHODS FOR MANAGING LAND AREA QUANTITY AND QUALITY USING GEOSPATIAL ANALYSIS TECHNOLOGIES - Akhmedova Muhayyo Shavkatovna (TADQIQOTLAR, 2025)
Abstract: The rapid advancement of geospatial analysis technologies has transformed land management practices by offering precise and efficient tools for monitoring land area quantity and quality. This study explores the integration of key geospatial technologies—Remote Sensing (RS), Geographic Information Systems (GIS), Artificial Intelligence (AI), and the Internet of Things (IoT)—in improving land assessment and sustainable resource management. Through a detailed analysis of current methods, we identify how these technologies enhance soil classification, land cover monitoring, and urban planning. Furthermore, the paper addresses existing challenges, including data integration complexities and the need for standardized methodologies. Our findings suggest that combining geospatial technologies with AI- driven analysis improves accuracy, efficiency, and long-term land management strategies. This study contributes to the ongoing discourse on sustainable land use, offering insights for policymakers and researchers aiming to optimize geospatial practices.